Intelligent Computer Graphics 2012 - Plemenos, Dimitri; Miaoulis, Georgios (Studies in Computational Intelligence, 2013)
In Computer Graphics, the use of intelligent techniques started more recently than in other research areas. However, during these last two decades, the use of intelligent Computer Graphics techniques is growing up year after year and more and more interesting techniques are presented in this area.   The purpose of this volume is to present current work of the Intelligent Computer Graphics community, a community growing up year after year. This volume is a kind of continuation of the previously published Springer volumes "Artificial Intelligence Techniques for Computer Graphics" (2008), "Intelligent Computer Graphics 2009" (2009), "Intelligent Computer Graphics 2010" (2010) and "Intelligent Computer Graphics 2011" (2011).   Usually, this kind of volume contains, every year, selected extended papers from the corresponding 3IA Conference of the year. However, the current volume is made from directly reviewed and selected papers, submitted for publication in the volume "Intelligent Computer Graphics 2012". This year papers are particularly exciting and concern areas like plant modelling, text-to-scene systems, information visualization, computer-aided geometric design, artificial life, computer games, realistic rendering and many other very important themes.  .